1999
DOI: 10.1039/a902279a
|View full text |Cite
|
Sign up to set email alerts
|

Spin isomerisation of para-substituted phenyl cations

Abstract: The singlet and triplet potential energy surfaces of a series of p-X-substituted aryl cations (X ‫؍‬ H, CN, CH 3 , F, OH, NH 2 ) are investigated computationally at the B3LYP/6-31G(d) level of theory. The first four species are found to be ground state singlets, the last has a triplet ground state, and the spin states of the OH derivative are almost isoenergetic. The minimum energy crossing points (MECPs) between the two surfaces are found to lie very little above the higher of the two minima in all cases, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 35 publications
2
61
0
Order By: Relevance
“…Yield 0.7 g, 89%. 4-(4-Phenyl-bytyl)-pyridine (19) was prepared by hydrogenation of (0.086 g, 0.41mmol) of the free base of 2 in 3 ml of EtOH at 1 atm and room temperature, in the presence of 0.015 g of 5% Pd/C catalyst. After 24 h stirring the catalyst was filtered off, the resulting solution was concentrated in vacuum, affording a crystalline colorless product in 93% yield (0.080g).…”
Section: Synthetic Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yield 0.7 g, 89%. 4-(4-Phenyl-bytyl)-pyridine (19) was prepared by hydrogenation of (0.086 g, 0.41mmol) of the free base of 2 in 3 ml of EtOH at 1 atm and room temperature, in the presence of 0.015 g of 5% Pd/C catalyst. After 24 h stirring the catalyst was filtered off, the resulting solution was concentrated in vacuum, affording a crystalline colorless product in 93% yield (0.080g).…”
Section: Synthetic Preparationmentioning
confidence: 99%
“…Thus it was found that in the case of phenyl cation the singlet-triplet splitting is relatively small and with a right choice of substituents at the phenyl ring can even be reversed [19]. The geometry for the cross-point between singlet and triplet has been calculated as well as spin orbit coupling for this transient structure [20].…”
mentioning
confidence: 97%
“…Although there are, a priori, no reasons why the principle should not apply in such cases, this does not appear to be a generally appreciated phenomenon. We previously discussed Hammond's postulate to rationalize trends in spin-isomerization barriers for a series of para-substituted phenyl cations, [24] but there do not appear to have been other mentions in the context of spin-forbidden processes.…”
Section: Comparison Of Energies and Geometries For The Mecp And Insermentioning
confidence: 97%
“…Similarly, the presence of G4 level singlet state imaginary frequencies for the p-hydroxy and thiophenyl cations not only prevents comparison with the E S-T estimates for these compounds in ref. [18,19], but also questions whether they have a gas phase singlet state potential energy well.…”
mentioning
confidence: 99%